(untitled) (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
The translation of poetic texts involves the complex task of reproducing both semantic content and aesthetic form. Among the essential poetic elements, rhythm and melody play a crucial role in shaping the expressive and emotional impact of a poem. This paper examines the poetic function of rhythm and melody in source texts, their reconstruction in translated texts, and the influence of the translator’s individual style. Employing a qualitative comparative method, the study analyzes selected poetic examples, including Persian and English verse, with particular attention to structural, phonetic, and stylistic transformations. The findings indicate that while full equivalence is unattainable, effective poetic translation relies on adaptive strategies and the creative competence of the translator. The study highlights the translator’s role as both interpreter and co-creator of the poetic text.